Introduction of a dedicated team increases the success rate of external cephalic version: A prospective cohort study. (May 2019) - Thissen, Daniek; Swinkels, Pauline; Dullemond, Remke C.; van der Steeg, Jan Willem
Abstract: Objective: To investigate the influence of a dedicated team on the success rate of external cephalic version and mode of delivery. Study design: This prospective cohort study included 673 women with a singleton fetus in breech presentation who underwent external cephalic version between January 2013 and December 2017 at Jeroen Bosch Hospital, 's-Hertogenbosch, The Netherlands. In January 2014, a dedicated team consisting of six gynaecologists and six midwives was introduced at the study clinic. The success rate of external cephalic version and mode of delivery were analysed. In addition, predictors for success were examined by logistic regression analysis. Successful external cephalic version was defined as fetal cephalic presentation immediately following the procedure. Results: Following the introduction of a dedicated team in 2014, the success rate of external cephalic version increased from 39.8% in 2013 to 69.5% in 2017 ( p < 0.001), with the greatest increase in nulliparous women (from 23.5% to 58.5%, p = 0.002). Over the 5-year study period, the vaginal delivery rate after external cephalic version increased from 43% in 2013 to 71% in 2017 ( p < 0.05). The rate of caesarean section after external cephalic version decreased from 55% to 27% ( p < 0.05). Anterior placenta [odds ratio (OR) 0.7, 95% confidence interval (CI) 0.48‒0.97] and complete breech (OR 0.2, 95% CI 0.07‒0.90) were significantly associated with a lower success rate. Conclusions: This study showed that introduction of a dedicated team led to a significant increase in the success rate of external cephalic version, and a significant decrease in the rate of caesarean section for women presenting with breech in pregnancy.